Measure Life Satisfaction : A Rasch Model Approach to Validation Instrument - Nasution, Salsabila; Ardi, Zadrian; Daharnis, Daharnis; Syahril, M. Fiqri; Putra, Ade Herdian (International Journal of Applied Counseling and Social Sciences, 2025)
Low life satisfaction can lead to serious mental health problems, including depression and anxiety, which can negatively impact quality of life. This study aims to develop and validate an instrument from Diener that can be used to measure life satisfaction accurately and reliably using the Rasch Model approach. This research method involved 70 participants representing various backgrounds, both men and women. The collected data were analyzed using the Rasch Model to evaluate scale accuracy, validity, reliability, and undimensionality on the life satisfaction scale. The results of this study explain that out of 7 scale item choices, there are three item choices on the life satisfaction scale that are inappropriate, namely scales 3, 4 and 5 which do not have peaks. The validity and reliability results show that 5 items are valid and reliable with the results of the validity value meeting the validity and reliability criteria resulting in a Cronbach's alpha value obtained of 0.83 which means it is in the good category. Furthermore, the findings of the dimensional test tested with standardized residuals are known to have a value of 65.1%. Assuming these criteria are met, the life satisfaction instrument meets the 20% threshold for the unidimensionality test.